An outline for a constitutional settlement in Sri Lanka - Marasinghe, M. L.; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2003)
On safeguarding the civil rights of Tamils in Sri Lanka.
Microfiche.
Keywords: Tamil (Indic people) -- Civil rights -- Sri Lanka